HARNESSING VOLCANIC ASH-BASED FORMULATION TO IMPROVE THE GROWTH AND YIELD OF MAIZE (Zea mays) UNDER CONTRASTING SOIL TEXTURES - Vinoth KN; Jerlin R; Djanaguiraman M; Eevera T; Manonmani V; Jeya Sundara Sharmila D (Journal of Animal and Plant Sciences, 2025)
As the global population is on the rise, food production must double by 2050 to meet demand. The excessive use of fertilizer for increasing the soil fertility leads to soil degradation and soil microbial diversity reduction. To address this issue, appropriate eco-friendly fertilizer management strategies without comprising the yield should be identified. With this notion, the study was taken up with volcanic ash-based formulation to increase the growth and productivity of maize in a sustainable way. Volcanic ash was tried both as seed coating and foliar spray to improve the productivity of maize. A laboratory experiment was conducted to optimize the dosage for seed coating using volcanic ash-based formulation, with different concentrations viz., 0, 2, 4, 6, 8 and 10 ml kg-1 of seeds. The results indicated that seed coating with volcanic ash @ 10 ml kg-1 of seeds significantly improved seed quality, yielding a maximum germination rate of 100%, shoot length of 23.2 cm, root length of 29.1 cm, dry matter production of 2.2 g seedlings-10 and seedling vigour index I of 5230. Following the standardization of the optimal seed coating dosage, field trials were conducted with the best performed treatment at two locations with different soil types viz., Department of Seed and Technology farm (E1) with sandy clay loam and Farmers field (E2) with sandy loam during November 2023 to February 2024. The combination of seed coating (10 ml kg-1) and foliar application (500 L ha⁻¹) on the 30th and 50th days after sowing with volcanic ash-based formulation showed the best results. In E1, this treatment recorded higher plant height (241 cm), dry matter (93.5 g plant⁻¹), crop growth rate (5.794 g m⁻² day⁻¹), 100-seed weight (33.0 g) and seed yield (6556 kg ha⁻¹). In E2, plant height (224 cm), dry matter (88.88 g plant⁻¹), crop growth rate (5.442 g m⁻² day⁻¹), 100-seed weight (32.38 g) and seed yield (6073 kg ha⁻¹) were recorded. Thus, it has been concluded that, volcanic ash formulation could be used as a potential base for the supplementation of nutrients to both seeds and plants in a sustainable approach amidst the chemical-based fertilizers.
Keywords: Maize; volcanic ash; coating; protein; α-amylase